Demythologizing de Gaulle: History as Myth and Myth as Hermeneutic in France after Vichy and Algerian Independence. Issue 1 (March 2022) - Tynan, Avril
Abstract : History, like fiction, is a narrative interpretation of events, and its writing or telling of the past is always mediated from a present position. The narratological turn in historical discourse from the 1960s challenged the assumption that accounts of the past were the objective accumulation of documented facts and emphasized the ideological mediation of historiography. With a focus on Roland Barthes's poststructuralist theory of myth as a hermeneutic structure for historical interpretation, this article argues that demythologization is less an elimination of ideological structures than an illumination; a counter- or re-mythologization that perpetuates interpretative work. As a demythologizing critique of Charles de Gaulle's myth of post-Occupation resistancialism, Michel Déon's Les Poneys sauvages (1970/2010) undermines the myth of a unanimous and united France and opens up spaces of ambiguity and subjectivity that reveal interpretative conflicts over the historical narratives of the Second World War and the Algerian War of Independence. Abstract : Comme la fiction, l'histoire présente un récit d'événements qui, abordé du présent, sera sujet à l'interprétation du narrateur. La mise en question de l'histoire comme accumulation objective de faits survint à partir des années 60 lorsque le tournant narratif dans les sciences humaines insistait sur le rôle interprétatif de l'historiographie. À l'instar de Roland Barthes et de sa théorie post-structuraliste du mythe comme herméneutique, cet article propose que la démythologisation ne fasse pas moins disparaître les structures idéologiques qu'elle les fait apparaître; il y est plutôt question de contre- ou ré-mythologisation qui perpétue le travail de l'interprétation. Les Poneys sauvages (1970/2010), de Michel Déon, propose une critique du mythe résistancialiste de Charles de Gaulle, érigé au cours des années après-guerres, en sapant au mythe de la France unanime et unifiée et ouvrant des lieux d'ambiguïté et subjectivité qui révèlent des conflits interprétatifs au sein de l'histoire – dans les deux sens – de la Deuxième Guerre Mondiale et la Guerre d'Algérie.